The Prevalence and Risk Factors Associated with the Presence of Antibiotic Residues in Milk from Peri-Urban Dairy Cattle Farms in Kathmandu, Nepal - Erda E. Rame Hau; Minu Sharma; Bal K. Sharma Khanal; Peter D. Sly; Deirdre Mikkelsen; Nicholas Clark; Ricardo J. Soares Magalhães (Antibiotics)
Background/Objectives: The presence of antibiotic residues (ARs) in animal products such as milk can be an important driver of antimicrobial resistance in commensal and pathogenic bacteria. Previous studies on ARs in Nepal have demonstrated the presence of ARs in milk samples but without further characterization of the samples for risk factor analysis. This study aimed to quantify the prevalence and risk factors for the presence of ARs in 140 peri-urban dairy farms in Kathmandu, Nepal, included in a cross-sectional survey in 2019 to estimate farm-level AR prevalence. Results: Our results reveal the presence of ARs of sulfamethazine (61%), sulfamethoxazole (53%), ciprofloxacin (46%), and enrofloxacin (42%). Furthermore, of those samples positive for sulfamethazine, sulfamethoxazole, and ciprofloxacin, 81%, 42%, and 42%, respectively, exceeded the maximum residue limit (MRL). While samples taken from farms where staff administered antibiotics were less likely to have single drug residues and multidrug residues (two, three, and four drugs), farms with more workers were more likely to have single residues. Moreover, samples from farms with a higher number of calves and milking cows were more likely to contain single and multiple residues exceeding the MRL, while milk from farms with higher numbers of dry cows and farmers reported by a visiting chemist were less likely to have multidrug residues exceeding the MRL. Methods: High-performance liquid chromatography was conducted on bulk milk samples from farms for an AR analysis, revealing positive results. Additionally, a structured questionnaire and direct farmer interviews were used to collect data on farm biosecurity and farming practices, animal health and hygiene, antibiotic usage (AMU), and attitudes and practices towards antibiotic stewardship. Conclusions: Ultimately, this study provides evidence on the role of modifiable ARs risk factors in the peri-urban milk industry of Kathmandu, which can serve as a foundation for developing improved antimicrobial stewardship guidelines and designing intervention measures to reduce the public health risk posed by ARs in milk sold in Kathmandu, Nepal.